How to Measure Procedural Knowledge for Solving Biodiversity and Climate Change Challenges - Lisa Richter-Beuschel; Ingo Grass; Susanne Bögeholz (MDPI AG, 2018)
To cope with biodiversity and climate change challenges, Education for Sustainable Development (ESD) needs to emphasize knowledge that considers multiple perspectives. Optimizing teacher education requires knowledge about the prerequisites of student teachers. The latter includes content knowledge with respect to Sustainable Development (SD). Apart from situational and conceptual knowledge, procedural knowledge (containing solution strategies) is of special interest, but it is much more difficult to measure. Thus, this study aims at developing a refined procedure to measure SD-relevant procedural knowledge and to define a measure for such knowledge, including a suitable benchmark for its evaluation. As SD-relevant knowledge, the SD challenges biodiversity loss and climate change were focused on. For operationalizing these challenges, the highly relevant contexts insects and pollination and peatland use were chosen. For both SD challenges and contexts, potential solution strategies were identified by a literature review. A procedure was then tested to measure procedural knowledge. The procedure includes a two-round expert survey (Delphi approach) with an in-between think-aloud study with student teachers. The described innovative procedure resulted in a measure (18 items) to assess procedural knowledge of student teachers via effectiveness estimations of provided solution strategies. This measure contains procedural knowledge items that are related to prior presented scenarios regarding the two contexts and a benchmark to evaluate these items. The benchmark derives from the second round of the Delphi study. The procedure and the developed final instrument include expertise from multiple disciplines such as ESD, SD, biodiversity, insect and pollination, climate change and peatland use. The sophisticated procedure can be transferred to challenging measurement developments. Furthermore, the measure provided for SD-relevant knowledge can be applied to other target groups in upper secondary and in higher education within ESD.